1993
DOI: 10.1111/j.1600-0773.1993.tb00303.x
|View full text |Cite
|
Sign up to set email alerts
|

Human Sperm Motility is Affected by Plasticizers and Diesel Particle Extracts

Abstract: In order to test various drugs and possibly hazardous compounds on living cells in vitro a system with human spermatozoa was employed. A population of human spermatozoa was transferred into a defined medium by a swim-up procedure or by separation on a Percoll gradient. Such a population is rather homogenous with respect to motility characteristics and was found to be useful for this purpose. Different modes of response were recorded, indicating various effect mechanisms. Effects of various phthalates used as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 37 publications
1
37
0
1
Order By: Relevance
“…This study assessed changes in many androgenic endpoints and found that only DEHP, BBP and to a lesser degree DINP induced alterations in all aspects of androgen-regulated male reproductive endpoints. Exposure to diethyl hexyl and dibutyl phthalates is associated with adverse effects on sperm motility (Fredricsson et al, 1993). Animal studies consistently demonstrated that phthalate esters are male reproductive toxicants (Park et al, 2002), with exposure associated with testicular atrophy, spermatogenetic cell loss, and damage to the Sertoli cell population.…”
Section: Phthalates Estersmentioning
confidence: 99%
“…This study assessed changes in many androgenic endpoints and found that only DEHP, BBP and to a lesser degree DINP induced alterations in all aspects of androgen-regulated male reproductive endpoints. Exposure to diethyl hexyl and dibutyl phthalates is associated with adverse effects on sperm motility (Fredricsson et al, 1993). Animal studies consistently demonstrated that phthalate esters are male reproductive toxicants (Park et al, 2002), with exposure associated with testicular atrophy, spermatogenetic cell loss, and damage to the Sertoli cell population.…”
Section: Phthalates Estersmentioning
confidence: 99%
“…Occupational activities involving exposure to specific chemicals or expositions to toxicants may impair male reproductive health and cause infertility in humans [27,37,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58].…”
Section: Introductionmentioning
confidence: 99%
“…While many studies have shown reproductive damage in animals exposed to DEHP, the effects DEHP have not been investigated among humans, although the study by Fredricsson et al (4) did find a decrease in sperm motility as a result of exposing human sperm cells to DEHP in vitro.…”
mentioning
confidence: 89%